Varianti testuali di «Pescatore»: da Marco Negri a Pierangelo Bertoli (e oltre) (Carte Romanze, 2024)
The article proposes the examination of the textual variants of Pescatore, a musical piece composed in 1980 by Marco Negri in collaboration with Pierangelo Bertoli and brought to success by Pierangelo Bertoli himself in a duet with Fiorella Man-noia, from its genesis to the rewritings and revivals of the subsequent decades.
Keywords: Pescatore; Marco Negri; Pierangelo Bertoli; Fiorella Mannoia; textual variants